2007
DOI: 10.1093/jxb/erl245
|View full text |Cite
|
Sign up to set email alerts
|

Transcript profiles at different growth stages and tap-root zones identify correlated developmental and metabolic pathways of sugar beet

Abstract: Field-grown sugar beets were analysed for morphological characters, sucrose content, and reproducible transcript profiles by macroarray analyses with 11,520 unique sugar-beet cDNA targets in two different years. Seasonal differences were partly compensated by expressing sampling dates as thermal time. During early beet development the number of cambial rings, root length, and sucrose concentration had already achieved >40% of their final values. Sucrose levels rose from 10% to 17% over the thermal time of 1300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
24
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 56 publications
12
24
1
Order By: Relevance
“…On tissue sections of the sampled sugar beet roots, 3–5 secondary cambium rings could be seen (Additional file 2). A mature sugar beet root consists of about 12 secondary cambium rings, where the first 8 cambium rings develop during the first 8 weeks [20]. Our results verified that the plants sampled were an appropriate material for this study.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…On tissue sections of the sampled sugar beet roots, 3–5 secondary cambium rings could be seen (Additional file 2). A mature sugar beet root consists of about 12 secondary cambium rings, where the first 8 cambium rings develop during the first 8 weeks [20]. Our results verified that the plants sampled were an appropriate material for this study.…”
Section: Resultssupporting
confidence: 77%
“…For example, mutants or silencing of these two genes as well as transgenic silencing studies of Arabidopsis and pea display low starch content, but not a complete loss of starch accumulation [31-33]. Similarly as found in this study, expression of some of the genes encoding for these key enzymes can be found as expressed in sugar beet when assessing supplementary information of Bellin et al [20]. Generally, support functions for starch synthesis such as genes encoding transporters for hexose phosphates and energy in the form of ATP were found to be less expressed in sugar beet than in parsnip tap-root although a complete lack of expression only was seen for a couple of transcripts.…”
Section: Discussionsupporting
confidence: 68%
“…ESTs (21 321) representing 13 618 genes have been cloned from sugar beet (3 February 2005 release, http://compbio. dfci.harvard.edu/tgi/cgi-bin/tgi/gimain.pl?gudb=beet; Herwig et al, 2002;Bellin et al, 2007). There are 26 870 ESTs deposited in the GenBank (accessed on 13 November 2007), of which about 20% are estimated to represent defence, signal transduction and secondary product synthetic genes.…”
Section: Development Of Transgenic Technologymentioning
confidence: 99%
“…No clear correlation with sugar yield was found for simple traits such as number and width of rings or parenchyma cell size at harvest (Draycott, 2006), even though several studies argued that, with shorter distances between phloem and storage tissues, a higher sucrose content should be achievable (Milford, 1973; Wyse, 1979; Doney et al, 1981). Also cDNA cloning of extracellular and vacuolar sucrose cleaving enzymes revealed a change in the mechanisms of the functional unloading pathways during the first weeks of beet development, and transcript profiles revealed developmental and metabolic changes at similar or later age (Godt and Roitsch, 2006; Bellin et al, 2007; Trebbi and Mcgrath, 2009). However, it could not be correlated with the development of structural traits such as tissue volume or growth rates.…”
Section: Discussionmentioning
confidence: 99%